2004
DOI: 10.1002/jsfa.1728
|View full text |Cite
|
Sign up to set email alerts
|

Biological activities of the essential oil and methanolic extract of Micromeria fruticosa (L) Druce ssp serpyllifolia (Bieb) PH Davis plants from the eastern Anatolia region of Turkey

Abstract: The in vitro antimicrobial and antioxidant activities of the essential oil and methanolic extract of Micromeria fruticosa ssp serpyllifolia as well as the composition of the essential oil were examined. The essential oil exhibited activity against 14 bacteria, three fungi and a yeast, with minimal inhibitory concentration (MIC) values ranging from 31.25 to 125 µl ml −1 , whilst the methanolic extract was inactive. Antioxidant activity was measured by two methods, namely scavenging of the free radical DPPH and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
75
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(79 citation statements)
references
References 19 publications
3
75
0
1
Order By: Relevance
“…The data of the study clearly indicated that the essential oil of Satureja hortensis plant has a strong a DD = diameter of disc diffusion (mm); OFX = Ofloxacin (10 µg/disc); SCF = sulbactam (30 µg) + cefperazone (75 µg) (105 µg/disc) and NET = Netilmicin (30 µg/disc) were used as positive reference standards antibiotic discs (Oxoid) b DD = inhibition zone in diameter (mm) around the discs (6 mm) impregnated with 300 µg/disc of methanol extract c DD =inhibition zone in diameter (mm) around the discs (6 mm) impregnated with 10 µl of essential oil d minimal inhibitory concentrations as (µg/ml) e MIC= maxipine (µg/ml) was used as reference antibiotic in micro well dilution assay (Sigma) (Tables 2 and 3). This observation supports the hypothesis that the essential oil of plants contains more antimicrobial substances than their extracts including water, methanol, ethanol, and hexane extracts (Ahmad et al 1998;Eloff 1998;Gulluce et al 2004b;Ozer et al 2006). The maximal inhibition zones and MIC values for bacterial strains, which were sensitive to the essential oil of Satureja hortensis, were in the range of 10-38 mm, and 15.62-250 µl/ml ( Table 2).…”
Section: Resultssupporting
confidence: 74%
“…The data of the study clearly indicated that the essential oil of Satureja hortensis plant has a strong a DD = diameter of disc diffusion (mm); OFX = Ofloxacin (10 µg/disc); SCF = sulbactam (30 µg) + cefperazone (75 µg) (105 µg/disc) and NET = Netilmicin (30 µg/disc) were used as positive reference standards antibiotic discs (Oxoid) b DD = inhibition zone in diameter (mm) around the discs (6 mm) impregnated with 300 µg/disc of methanol extract c DD =inhibition zone in diameter (mm) around the discs (6 mm) impregnated with 10 µl of essential oil d minimal inhibitory concentrations as (µg/ml) e MIC= maxipine (µg/ml) was used as reference antibiotic in micro well dilution assay (Sigma) (Tables 2 and 3). This observation supports the hypothesis that the essential oil of plants contains more antimicrobial substances than their extracts including water, methanol, ethanol, and hexane extracts (Ahmad et al 1998;Eloff 1998;Gulluce et al 2004b;Ozer et al 2006). The maximal inhibition zones and MIC values for bacterial strains, which were sensitive to the essential oil of Satureja hortensis, were in the range of 10-38 mm, and 15.62-250 µl/ml ( Table 2).…”
Section: Resultssupporting
confidence: 74%
“…Minimum inhibitory concentration (MIC) values of essential oils against bacterial strains were determined based on a micro-well dilution method as previously described [22]. The essential oils, dissolved in 10% dimethyl sulfoxide (DMSO), were first diluted to the highest concentration (40 µl/ml) to be tested, and then serial twofold dilutions were made in a concentration range from 0.078 to 40 µl/ml in test tubes.…”
Section: Micro-well Dilution Assaymentioning
confidence: 99%
“…The tests were repeated three times to ensure reliability. The plates were incubated at 37 o C for 24 h and the inhibition zones were checked [19].…”
Section: Determination Of Antimicrobial Activity Of Essential Oilmentioning
confidence: 99%